PENGELOLAAN DATA PRODUKSI BERBASIS WEB PADA CV. SUMBER PROTEINA BANDAR LAMPUNG - T M Zaini; Driya Wiryawan; Aryadi Aryadi (Jurnal Informatika, 2021)
CV. Sumber Proteina is a company that engaged in animal husbandry that produces and distributes chicken eggs. The reporting process at this company is still done manually, so it takes quite a long time to be able to provide reporting data until it reaches the head office. Thus the report need long time to reach the manager. Based on this, this company need a website that can facilitate the delivery of reports and data processing reports, so as to minimize the time of sending data and managing data reports. Management of production data at this company can help decision-making parties at the management level to speed up the process of reporting and processing production data. The system development uses the RAD (Rapid Application Development) model and the design tool is the Unified Modeling Language (UML). The stages for developing RAD system begin at the planning requirements stage, the user design, the Rapid Construction stage and the cutover or system testing stage. The results of this study are in the form of a system that can provide information on the availability of chicken eggs and can also be used online for consumers.Keywords—Data Processing, Production, Report, Website.